Pengaruh Pertumbuhan Asset dan Operating Leverage terhadap Debt to Equity Ratio pada Perusahaan Sektor Industri yang Terdaftar di Bursa Efek Indonesia - Adi Maulana Rachman (CV. Creative Tugu Pena, 2024)
The purpose of this research is to know the influence asset growth and operating leverage the capital structure, in which the author takes a sample of companies listed on the Indonesia stock exchange the period 2011-2014, as many as 29 companies. The method used is quantitatively, where the methods used to research on population or specific samples, the instruments used are the financial statements of the company manufacturing of miscellaneous industry sectors of the sample of this research. The research results, is partial to the variable asset growth obtained the number thitung of 4,097 > ttabel 1,976 with significance 0.000 < 0.05 thus influential asset growth significantly to the value of the capital structure, while for variable Operating Leverage obtained thitung of 0.991 < 1.976 ttabel , which means the operating leverage influential insignificant to the capital structure. As for simultaneous test results, obtained fhitung of 36.879 > ftabel 3.06 with significance 0.00 < sig 0.05. Thus the asset growth and operating leverage together influential significantly to the capital structure.